Exergy Analyses of Onion Drying by Convection: Influence of Dryer Parameters on Performance - María Castro; Celia Román; Marcelo Echegaray; Germán Mazza; Rosa Rodriguez (Entropy, 2018)
This research work is concerned in the exergy analysis of the continuous-convection drying of onion. The influence of temperature and air velocity was studied in terms of exergy parameters. The energy and exergy balances were carried out taking into account the onion drying chamber. Its behavior was analyzed based on exergy efficiency, exergy loss rate, exergetic improvement potential rate, and sustainability index. The exergy loss rates increase with the temperature and air velocity augmentation. Exergy loss rate is influenced by the drying air temperatures and velocities because the overall heat transfer coefficient varies with these operation conditions. On the other hand, the exergy efficiency increases with the air velocity augmentation. This behavior is due to the energy utilization was improved because the most amount of supplied energy was utilized for the moisture evaporation. However, the exergy efficiency decreases with the temperature augmentation due to the free moisture being lower, then, the moisture begins diffusing from the internal structure to the surface. The exergetic improvement potential rate values show that the exergy efficiency of onion drying process can be ameliorated. The sustainability index of the drying chamber varied from 1.9 to 5.1. To reduce the process environmental impact, the parameters must be modified in order to ameliorate the exergy efficiency of the process.